2019
DOI: 10.1002/jmd2.12059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurophysiological characteristics of heterozygous NPC1 carriers

Abstract: Niemann‐Pick disease type C (NPC) is an uncommon lysosomal storage disorder, which is characterized neuropathologically by cholinergic dysfunction and presents clinically with a broad series of neurological signs and symptoms. NPC is inherited as an autosomal recessive trait, caused by mutations in the NPC1 or NPC2 genes. However, recent reports have raised concerns on heterozygous NPC1 gene mutation carriers, which historically have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…First, changes in both autophagy and oxidative stress both play a role in the cellular damage seen in the disease ( Vázquez et al, 2012 ; Sarkar et al, 2013 ); the effects of alcohol on these pathways has already been discussed in detail in preceding sections. Second, there are noted deficits in cholinergic signaling in Niemann-Pick Type C patients ( Benussi et al, 2019 ); alcohol also has a potent effect on cholinergic activity. Intermittent, or binge, exposure to alcohol in adolescence reduces the number of neurons that express choline acetyltransferase, the enzyme that is responsible for the production of acetylcholine ( Swartzwelder et al, 2015 ).…”
Section: Putative Roles Of Alcohol In Specific Rare Neurodegenerative Diseasesmentioning
confidence: 99%
“…First, changes in both autophagy and oxidative stress both play a role in the cellular damage seen in the disease ( Vázquez et al, 2012 ; Sarkar et al, 2013 ); the effects of alcohol on these pathways has already been discussed in detail in preceding sections. Second, there are noted deficits in cholinergic signaling in Niemann-Pick Type C patients ( Benussi et al, 2019 ); alcohol also has a potent effect on cholinergic activity. Intermittent, or binge, exposure to alcohol in adolescence reduces the number of neurons that express choline acetyltransferase, the enzyme that is responsible for the production of acetylcholine ( Swartzwelder et al, 2015 ).…”
Section: Putative Roles Of Alcohol In Specific Rare Neurodegenerative Diseasesmentioning
confidence: 99%
“…Some of these studies showed common clinical manifestations between NPC and PD, such as supranuclear gaze palsy and dementia [66]. Moreover, a recent study showed subclinical deficits in cognition in NPC1 carriers that correlated with impairment of cholinergic circuits [67]. NPC has not explicitly been identified in genetic association studies of large PD cohorts.…”
Section: Links Between Pd and Multiple Lsdsmentioning
confidence: 99%